2010
DOI: 10.1007/s13364-010-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and seasonal variability in feeding behaviour of a small herbivorous rodent

Abstract: Foraging strategies have traditionally been modelled as a result of food selection in response to one factor, as for instance resource availability, deterrent compounds or nutrients. Thus, a trade-off is assumed between plasticity (generalist strategy) and efficiency (specialist strategy). Nevertheless, several studies have demonstrated that animals cope behaviourally with food supply variation. For instance, desertdwelling rodents partially compensate for nutritional bottlenecks through diet selection. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
9
0
8
Order By: Relevance
“…Standardised means and standard errors for stomach, small intestine, caecum, colon and total gastrointestinal tract are detailed in Table 3. DISCUSSION In order to maintain their energy and nutritional balance, animals cope with variations in the trophic scenario through behavioural and physiological adjustments that translate into their dietary choices (Sherry 1990;Chambers et al 1995;Kyriazakis et al 1999;Sassi et al 2011). Furthermore, all this occurs under temperature and other climatic factors that impose diverse energy demands and restrictions to the foraging behaviour (Caraco et al 1990;Murray & Smith 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Standardised means and standard errors for stomach, small intestine, caecum, colon and total gastrointestinal tract are detailed in Table 3. DISCUSSION In order to maintain their energy and nutritional balance, animals cope with variations in the trophic scenario through behavioural and physiological adjustments that translate into their dietary choices (Sherry 1990;Chambers et al 1995;Kyriazakis et al 1999;Sassi et al 2011). Furthermore, all this occurs under temperature and other climatic factors that impose diverse energy demands and restrictions to the foraging behaviour (Caraco et al 1990;Murray & Smith 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, many studies indicate that laboratory rodents (rats and mice) show an increase in their activity under food deprivation, which is proportional to the severity of food restriction 64 . Because animals often face nutritional bottlenecks 65,66 , it is not surprising that under these circumstances, the physiological and behavioral adjustments observed in the current study could occur in wild life.…”
Section: Role Of Temperature and Nst From A Bioenergetic Perspectivementioning
confidence: 90%
“…Sassi et al (2007, 2010) demonstrated significant variations in morphological and physiological digestive traits, with large gastrointestinal chambers in cavies from El Leoncito and Matagusanos, which are exposed to comparatively low quality diets compared with animals from Villavicencio and Ñacuñán. Foraging behavior also changed thoroughly among the cited populations, and particular items were dominant in the different sites: mesquite forest in Matagusanos and Ñacuñan diets and creosotebush in El Leoncito and Villavicencio diets (Sassi et al, 2011). The latter result is especially interesting because it has been demonstrated that the phenolic resin of creosotebush affects negatively other rodent species (Dearing et al, 2001; Mangione et al, 2004).…”
mentioning
confidence: 99%